G385(P) Getting more from less: tackling work pressures faced by paediatric trainees. (25th October 2020) - Cooper, H; O'Keeffe, M; Aguirre, D; Steadman, S; Kenyon-Blair, D; Negrine, R; Goodyear, H; ,
Abstract : Aims: As part of a wider piece of work looking into the '8 High Impact Interventions to Improve the Working Lives of Junior Doctors' document from NHS Improvement we gathered data on trainees' experience of workplace pressures and what they felt would help them use their time more effectively. Methods: A voluntary questionnaire was designed based on '8 High Impact Actions to Improve the Working Environment for Junior Doctors' document by NHS Improvement. This was circulated on paper at trainees' regional teaching days and online via Survey Monkey from December 2018-March 2019. Results: Responses were received from 47% (143/306) of trainees. 74% (101/137) of trainees reported regularly (44% daily and 30% weekly) carrying out tasks they felt could be shared amongst a range of staff. These included: Blood tests, cannulas and blood gases (24%, 34/143) Writing/printing forms (11%, 15/143) Booking or chasing appointments (11%, 15/143) Restocking consumables (9%, 13/143) Fixing IT systems (8%, 11/143) Trainees reported having to duplicate documentation including: NIPE (newborn infant physical examination) documentation (22%, 29/134) Immunisation documentation (10%, 13/134) Copying admission notes from paper into Badger (neonatal online documentation) systems (8%, 11/134) When asked what trainees thought would help them manage the ever increasing workload, trainees' most common responses were: Better IT systems (18%, 25/134) Upskilling other team members (18%, 24/134) More support staff (15%, 20/134) More doctors (10%, 14/134) Conclusions: At a time when there are significant NHS pressures with staff facing increasing workloads, we felt a review of how the paediatric medical workforce is utilised was important. Our data highlights trainees' views on how their time is spent, and how a commitment to quality improvement projects e.g. procedure packs to avoid lost time looking for items and sharing of tasks across a wider multi-disciplinary team may help manage the current pressures more effectively. Such projects are now being undertaken in our region and we aim to feed these back to the wider community in the future.